An exact operator that knows its location - Anand, N.; Chen, Hongbin; Fitzpatrick, A. Liam; Kaplan, Jared; Li, Daliang (The journal of high energy physics, 2018)
A bstract We use conformal symmetry to define an AdS 3 proto-field ϕ as an exact linear combination of Virasoro descendants of a CFT 2 primary operator O . We find that both symmetry considerations and a gravitational Wilson line formalism lead to the same results. The operator ϕ has many desirable properties; in particular it has correlators that agree with gravitational perturbation theory when expanded at large c , and that automatically take the correct form in all vacuum AdS 3 geometries, including BTZ black hole backgrounds. In the future it should be possible to use ϕ to probe bulk locality and black hole horizons at a non-perturbative level.